Audit of Professional Competence of Automotive Productive Teachers Based on Teacher Competency Standards - Susatya, Edhy; Zuhaery, Muhammad; Hastuti, Sri; Suratno, Eko; Fachri, Fandi Faisyal; Dewi, Meirisa Isdiana; Sintawati, Buni Fitria (Journal of Vocational Education Studies, 2024)
Professional competence is a technical skill that must be mastered by productive Vocational School teachers. Unfortunately, to date no audit has been carried out. The aim of the research is to audit the level of professional competence of productive teachers in motorbike engineering and business based on teacher competency standards. The audit is focused on the knowledge aspect. The research method is quantitative. The population is productive teachers of motorbike engineering and business with a sample of five vocational schools using probability sampling. Data collection uses instruments. Data analysis uses statistics with the discrepancy evaluation model. Research procedure; problem identification, literature study, field observation, instrument creation, data collection, processing and conclusions. Research result; (1) 96.29% of teachers met the academic qualification requirements and 3.71% did not. Suitability of educational background with teaching obligations; 92.59% were appropriate and 7.41% were not appropriate. 33.33% of teachers are certified educators and 66.67% are not yet certified. (2) the results of teacher competency audits in the form of knowledge passports and training recommendations; 18.52% of less competent teachers are recommended to take basic training, 37.04% of moderately competent teachers are recommended to take intermediate training, 37.04% of competent teachers are recommended to take advanced training, and 7.40% of highly competent teachers are not recommended to take advanced training or professional development. The lowest mean sub-competency score was 2.4 in color maching, while the highest mean score was 3.7 in the battery sub-competency.